Assessment of Similarity in Antipsychotic Exposure‐Response Relationships in Clinical Trials Between Adults and Adolescents With Acute Exacerbation of Schizophrenia. (28th January 2020) - Kalaria, Shamir N.; Farchione, Tiffany R.; Mathis, Mitchell V.; Gopalakrishnan, Mathangi; Younis, Islam; Uppoor, Ramana; Mehta, Mehul; Wang, Yaning; Zhu, Hao
Abstract: Despite agreement that early‐onset schizophrenia is continuous with the adult‐onset form, quantitative relationships between antipsychotic exposure and clinical response are relatively unexplored in adolescents, compared to adults. Clinical efficacy data from second‐generation antipsychotic development programs (N = 5951 adults and N = 1035 adolescents ranging from 12 to 17 years old) were collected from available new drug applications submitted to the US Food and Drug Administration from 1993 to 2017. The developed disease–drug trial models adequately predicted the longitudinal trend in total positive and negative syndrome scale scores in both adults and adolescents using a Weibull placebo response, time‐delayed drug effect, and a Weibull structural dropout model. Maximum drug effect was similar between the two populations and was estimated to be between a range of 5% to 11% in adults and 5% to 7% in adolescents. Half maximal effective concentration parameter estimates also indicated similar exposure‐response relationships in adults and adolescents across all 4 antipsychotics. Simulated adolescent data using final model parameter estimates from the adult model were in agreement with adolescent observations. This analysis confirms similarity in exposure‐response for efficacy and could expedite the development of second‐generation antipsychotics for adolescents.